(3cJGH GdCSeGA GdeHgeI aj GdCfHG GdeMceIs - (3CHhHcQ CMeO Hf Ydj Hf KGHJ GdNWjH GdHZOGOjs; (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf, GHf CHj GdOfjG GdbQTj GdCehj (B( (3ehdGge(B) (3, GdHZOGOj, CHh HcQ,J (B281 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe CHhHcQ CMeO Hf Ydi Hf KGHJ s
(3BNQgG (B:s
(3hPdc gh SeGY YHOGdUeO Hf OGhO s
(3GfXQg HQbe (B579 (3JGQjNs
(3fSNI bhHdJ Ydi fSNI GHf GdfMGS eMeO Hf YHOGddg Hf GdMSf Hf WdMI GdHjSi HSeGYg ef daXgs
(3hgh KeGfjI CLRGA ai eLdO GHJOGA ef GdLRA GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs